An analysis of the impacts of Cretaceous oceanic anoxic events on global molluscan diversity dynamics. Issue 2 (10th April 2019) - Freymueller, Nicholas A.; Moore, Jason R.; Myers, Corinne E.
Abstract: Oceanic anoxic events (OAEs) are contemporaneous with 11 of the 18 largest Phanerozoic extinction events, but the magnitude and selectivity of their paleoecological impact remains disputed. OAEs are associated with abrupt, rapid warming and increased CO2 flux to the atmosphere; thus, insights from this study may clarify the impact of current anthropogenic climate change on the biosphere. We investigated the influence of the Late Cretaceous Bonarelli event (OAE2; Cenomanian/Turonian stage boundary; ~94 Ma) on generic- and species-level molluscan diversity, extinction rates, and ecological turnover. Cenomanian/Turonian results were compared with changes across all Cretaceous stage boundaries, some of which are coincident with less severe OAEs. We found increased generic turnover, but not species-level turnover, associated with several Cretaceous OAEs. The absence of a species-level pattern may reflect species occurrence data that are too temporally coarse to robustly detect patterns. Five hypotheses of ecological selectivity relating anoxia to survivorship were tested across stage boundaries with respect to faunality, mobility, and diet using generalized linear models. Interestingly, benthic taxa were consistently selected against throughout the Cretaceous regardless of the presence or absence of OAEs. These results suggest that: (1) the Cenomanian/Turonian boundary (OAE2) was associated with a decline in molluscan diversity and increase in extinction rate that were significantly more severe than Cretaceous background levels; and (2) no differential ecological selectivity was associated with OAE-related diversity declines among the variables tested here.